2024
DOI: 10.3389/fimmu.2023.1286632
|View full text |Cite
|
Sign up to set email alerts
|

Biological response of nonhuman primates to controlled levels of acute blood loss

Juhye Roh,
Eun Mi Park,
Haneulnari Lee
et al.

Abstract: IntroductionThe global shortage of human blood for medical use has prompted the development of alternative blood sources. Nonhuman primates (NHPs) are commonly used owing to their physiological similarities to humans. The objective of the current study was to establish a controlled-blood-loss model in NHPs to explore their clinical and biological responses.MethodsBlood was sequentially withdrawn from 10 cynomolgus monkeys (10, 14, 18, 22, and 25% of the total blood volume); their vital signs were monitored, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In our previous NHP blood-loss model study ( 14 ), we observed a significant increase in WBCs, including neutrophils, regardless of transfusion, likely owing to stress and compensatory mechanisms. The pRBC preparations used leukocyte-depletion filters, resulting in leukocyte counts below measurable limits ( Table 1 ).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In our previous NHP blood-loss model study ( 14 ), we observed a significant increase in WBCs, including neutrophils, regardless of transfusion, likely owing to stress and compensatory mechanisms. The pRBC preparations used leukocyte-depletion filters, resulting in leukocyte counts below measurable limits ( Table 1 ).…”
Section: Discussionmentioning
confidence: 54%
“…From all the NHPs, 25% of the total blood volume was removed, and the same amount of WT- or TKO-pRBCs (n=4 per group; male 2, female 2), or saline (n=2; male 1, female 1) as a control was administered to each NHP. The data and leftover samples of the two NHPs with 25% blood withdrawal in our previous study ( 14 ) were included in the control group (n=4). Vital signs and general symptoms were observed daily for three weeks from the day of blood withdrawal/transfusion (D0).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations